2020
DOI: 10.3390/molecules25225460
|View full text |Cite
|
Sign up to set email alerts
|

(E)-1-(Furan-2-yl)-(substituted phenyl)prop-2-en-1-one Derivatives as Tyrosinase Inhibitors and Melanogenesis Inhibition: An In Vitro and In Silico Study

Abstract: A series of (E)-1-(furan-2-yl)prop-2-en-1-one derivatives (compounds 1–8) were synthesized and evaluated for their mushroom tyrosinase inhibitory activity. Among these series, compound 8 (2,4-dihydroxy group bearing benzylidene) showed potent tyrosinase inhibitory activity, with respective IC50 values of 0.0433 µM and 0.28 µM for the monophenolase and diphenolase as substrates in comparison to kojic acid as standard compound 19.97 µM and 33.47 µM. Moreover, the enzyme kinetics of compound 8 were determined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…According to the cumulative docking simulation results, the 2,4-dihydroxyl substituent on the β -phenyl ring contributes to strong binding to tyrosinase through hydrogen bonding at the active site, implying that the 2,4-dihydroxyl substituent plays an important role in tyrosinase inhibition. In some compounds [53] , [58] , [61] , [62] , [64] , [66] , both hydroxyl groups of the 2,4-dihydroxyl substituent participate in hydrogen bonding as hydrogen bond donors, and in some compounds [49] , [60] , [61] , [67] only one of the two hydroxyls participates in hydrogen bonding as a hydrogen bond donor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the cumulative docking simulation results, the 2,4-dihydroxyl substituent on the β -phenyl ring contributes to strong binding to tyrosinase through hydrogen bonding at the active site, implying that the 2,4-dihydroxyl substituent plays an important role in tyrosinase inhibition. In some compounds [53] , [58] , [61] , [62] , [64] , [66] , both hydroxyl groups of the 2,4-dihydroxyl substituent participate in hydrogen bonding as hydrogen bond donors, and in some compounds [49] , [60] , [61] , [67] only one of the two hydroxyls participates in hydrogen bonding as a hydrogen bond donor.…”
Section: Resultsmentioning
confidence: 99%
“…During our studies on this topic over past decades, we have identified a number of benzylidene derivatives with the β-phenyl-α,β-unsaturated carbonyl scaffold more potently inhibit tyrosinase than kojic acid, a representative tyrosinase inhibitor ( Fig. 1 ) [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [29] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosinase is a copper‐dependent enzyme that catalyses the conversion of L‐tyrosine to L‐DOPA, which is the rate‐limiting step in melanin biosynthesis 34 . Previous studies have showed that tyrosine metabolism influences the development, differentiation and proliferation of melanocytes, formation and transportation of melanosomes and synthesis of melanin 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase is a copper-dependent enzyme that catalyses the conversion of L-tyrosine to L-DOPA, which is the rate-limiting step in melanin biosynthesis. 34 Previous studies have showed that tyrosine metabolism influences the development, differentiation and proliferation of melanocytes, formation and transportation of melanosomes and synthesis of melanin. 35 Our results showed that after Rab23 downregulation, the melanin level in B16F10 cells and tyrosinase activity stimulated by UVB were not significantly increased, We analysed the influence of siRab23 on melanogenesis induced by UVB irradiation at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Several tyrosinase inhibitor scaffolds have been studied over the past few decades, but none of them are used clinically [ 12 , 13 , 14 , 15 ]. During our past studies, we synthesized various derivatives with a phenyl-α,β-unsaturated carbonyl (PUSC) scaffold [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] with the aim of developing novel, potent tyrosinase inhibitors ( Figure 1 ). In B16F10 melanoma cells, all of these derivatives inhibited tyrosinase and melanogenic activity more potently than kojic acid, a representative tyrosinase inhibitor.…”
Section: Introductionmentioning
confidence: 99%